Impact of curcumin supplementation in monochromatic light on lipid serum profile of sexually mature female Magelang ducks - Kasiyati, K.; Sumiati, S.; Ekastuti, D. R.; Manalu, W. (Journal of the Indonesian Tropical Animal Agriculture, 2018)
An experiment was conducted to study the effect of curcumin supplementation inexpose monochromatic light on serum lipid concentrations of sexually mature female magelang duck. One hundred and ninety two female magelang ducks were assigned into a completely randomized design with a 4×4 factorial arrangement and each experimental unit was repeated 3 times, each with 4 female magelang ducks. The first factor was dose of curcumin supplementation consisted of 4 levels i.e., 0, 9, 18, and 36 mg/duck/day. The second factor was the color of monochromatic light consisted of 4 levels i.e., white, red, green, and blue colors. The data were analyzed by two-way ANOVA. The result showed that serum concentrations of triglyceride, cholesterol, very low density lipoprotein (VLDL), and low density lipoprotein (LDL) were lower (P<0.05) while high density lipoprotein (HDL) were higher (P<0.05) in experimental ducks supplemented with a curcumin dose of 36 mg/duck/day in variety of monochromatic light colors compared to control experimental ducks without curcumin supplementation. The curcumin doses of 18 or 36 mg/duck/day within red, green, or blue light had the potential to modulate lipid metabolism, as indicated by the increased serum concentration of HDL and the decreased serum concentrations of triglyceride, cholesterol, VLDL, and LDL of the experimental female magelang ducks.